Implementasi Terapi Pijat Swedia untuk Menurunkan Tingkat Kecemasan dan Menstabilkan Tanda-Tanda Vital Pada Pasien Di Ruang Intensive Care Unit (ICU) Rumah Sakit Prof. Dr. Margono Soekarjo: Case Study - Muslimah, Nida; Awaludin, Sidik; Kurniawan, Aji (Journal of Bionursing, 2019)
Background. Intensive Care Unit (ICU) is an inpatient room with patients who has critical disease and must be monitored every hour, attached devices, and intensive treatment. When the patient has woken up to a different room and attached devices such as ETT, OPA, mechanical ventilator, and others can cause anxiety to the patient. This anxiety can enhance the hemodynamic status, therefore it is necessary to have an independent nurse action, namely Swedish massage therapy to reduce the level of Anxiety and stabilize vital signs.Method. The method of implementation was used a case study with a cross sectional design. Total respondents were 6 respondents and divided into two groups, namely the intervention group 3 respondents and the control group 3 respondents. The implementation was conducted in ICU RSUD Prof. Dr. Margono Soekarjo.Result. There was a differentiation in anxiety level in the intervention group, respondents who feel quite anxious became a less anxious. The differentiation in hemodynamic status were more stable in the intervention group than in the control group.Conclusion. Swedish massage therapy can reduce anxiety levels and stabilize vital signs in patients in the ICU.